The effects of educational program on child care knowledge and behaviors of mothers of children under five years with pneumonia (Bangladesh Journal of Medical Science, 2010)
Objectives: This study was aimed to evaluate the effects of the educational program on child care knowledge and behaviors of mothers of children aged under five years. Materials and Methods: The quasi-experimental, pretest-posttest design was used to examine the effects of educational program on child care knowledge and behaviors of mothers of children under five years old with pneumonia. Fifty mothers of children under five years hospitalized with pneumonia were purposively assigned following standard procedure into either experimental or control group. Mothers of the study group received educational program together with children’s routine care, where as control group mothers just attended their children receiving treatment. Subsequently mothers’ knowledge, evaluated through structured Knowledge Questionnaire and behavioral information, through Behavioral Checklist Form were evaluated. Data were expressed as number (percent) and mean (SD) as appropriate. Demographic characteristics were analyzed by using frequency, percentage, mean, and standard deviation. Independent t-test and paired t-test were used to calculate statistical difference between groups as applicable. Results: Findings revealed that, subjects of both groups are homogenous in terms of demographic characteristics, but significant difference was observed regarding their mean (±SD) knowledge (25.04±5.81 vs 34.64±3.86, p